The transcriptome response of the ruminal methanogen Methanobrevibacter ruminantium strain M1 to the inhibitor lauric acid - Xuan Zhou; Marc J. A. Stevens; Stefan Neuenschwander; Angela Schwarm; Michael Kreuzer; Anna Bratus-Neuenschwander; Johanna O. Zeitz (BMC Research Notes, 2018)
Abstract Objective Lauric acid (C12) is a medium-chain fatty acid that inhibits growth and production of the greenhouse gas methane by rumen methanogens such as Methanobrevibacter ruminantium. To understand the inhibitory mechanism of C12, a transcriptome analysis was performed in M. ruminantium strain M1 (DSM 1093) using RNA-Seq. Results Pure cell cultures in the exponential growth phase were treated with 0.4 mg/ml C12, dissolved in dimethyl sulfoxide (DMSO), for 1 h and transcriptomic changes were compared to DMSO-only treated cells (final DMSO concentration 0.2%). Exposure to C12 resulted in differential expression of 163 of the 2280 genes in the M1 genome (maximum log2-fold change 6.6). Remarkably, C12 hardly affected the expression of genes involved in methanogenesis. Instead, most affected genes encode cell-surface associated proteins (adhesion-like proteins, membrane-associated transporters and hydrogenases), and proteins involved in detoxification or DNA-repair processes. Enrichment analysis on the genes regulated in the C12-treated group showed a significant enrichment for categories ‘cell surface’ and ‘mobile elements’ (activated by C12), and for the categories ‘regulation’ and ‘protein fate’ (represssed). These results are useful to generate and test specific hypotheses on the mechanism how C12 affects rumen methanogens.